Reproductive characteristics of Kansas Holstein herds grouped by rolling herd average - Edward P. Call; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1985)
An analysis of 635 Kansas Holstein herds with 41,426 cows indicated that the negative genetic antagonism between production and reproduction can be overcome with good management practices. As rolling herd average increased, only services per conception increased by 0.2 units. All other reproductive traits favored higher yearly production. Days to first service and cows not yet bred are the main factors responsible for less than ideal reproductive performance in Kansas Holstein herds.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Reproductive; Rolling herd average; Holstein; Conception rate